Hepatitis E virus genotype 3 is associated with gallstone-related disease. (3rd October 2019) - Karlsson, Miriam; Norder, Heléne; Bergström, Maria; Park, Per-Ola; Karlsson, Marie; Wejstål, Rune; Alsiö, Åsa; Rosemar, Anders; Lagging, Martin; Mellgren, Åsa
Abstract: Objective: Hepatitis E virus (HEV) genotype 3 is endemic in Northern Europe and despite a high seroprevalence of anti-HEV IgG antibodies among blood donors (≈17%), few clinical cases are notified in Sweden. Low awareness of hepatitis E and its possible symptoms may contribute to this discrepancy. The aim of this study was to investigate the prevalence of acute HEV infection among hospital admitted patients with abdominal pain and elevated liver enzymes. Materials and methods: During 2016–2017, 148 adult patients with serum alanine aminotransferase (ALT) or aspartate aminotransferase (AST) > twice normal levels were prospectively enrolled at surgical wards at three Swedish hospitals. Serum samples were analyzed for HEV RNA as well as anti-HEV IgM and IgG, and medical records were reviewed. Results: Six (6/148, 4.1%) patients were HEV infected confirmed by detectable HEV RNA, but only one of these patients had detectable anti-HEV antibodies. Four of the HEV infected patients were diagnosed with gallstone-related disease: three with biliary pancreatitis and one with biliary colic. The remaining two were diagnosed with bowel obstruction and pancreatic malignancy. Four HEV strains were typed by sequencing to genotype 3. Conclusions: This study identified acute HEV3 infection in 4% of the patients with elevated liver enzymes admitted to a surgical ward. HEV infection was not the solitary disease leading to hospitalization, instead it was found to be associated with other surgical conditions such as gallstone-related disease including biliary pancreatitis. Additionally, HEV RNA might be the preferential diagnostic tool for detecting ongoing HEV infection.